2020
DOI: 10.1177/1744987120951594
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-seeking behaviours in college students and young adults: a review

Abstract: Background/aims To review the literature on college students’ healthcare-seeking behaviours to uncover the current evidence and promote better healthcare-seeking behaviours and essentially better health outcomes in young adults. Methods The researchers conducted an extensive literature review using CINAHL, Cochrane, PubMed, EBSCOhost and Google Scholar in the years 2018 and 2019. The search was limited to the past 18 years (2000–2018) and to studies reported in the English language focused on the general healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(83 reference statements)
2
10
0
Order By: Relevance
“…In this study, more than 70% of the contacts were made by females. The finding is supported by the previous findings about females using more healthcare services compared with males 14 20 42. In a previous study, Finnish female university students reported more psychological and physical symptoms and use more sexual health services compared with males, which may explain the result 29.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, more than 70% of the contacts were made by females. The finding is supported by the previous findings about females using more healthcare services compared with males 14 20 42. In a previous study, Finnish female university students reported more psychological and physical symptoms and use more sexual health services compared with males, which may explain the result 29.…”
Section: Discussionsupporting
confidence: 80%
“…16 17 The basis of the preventative work in the FSHS is a two-staged health screening process, which includes an electronic Health Questionnaire (eHQ) provided to all university entrants and a subsequent health check, when necessary, based on the students' eHQ responses. 18 19 Previous research on university students' healthcare service utilisation is limited, 20 even though there are studies focusing on school-based healthcare of adolescents, not yet in universities. 21 Most research studying the effect of health checks on healthcare utilisation has focused on hospitalisations and very few have been conducted in the primary care context.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for ACEs and other health risks is especially germane to the present study’s target population (i.e., young adults), given low rates of primary care utilization and increased rates of high-risk behaviors [ 57 , 58 ]. Recent data show that young adults generally have a significant cardiovascular health risk resulting from heightened stress, poor diet, lack of sleep, decreased physical activity, and increased tobacco, alcohol, and drug use [ 59 ]. Compounding these known health risks is the deficient “transition of care” process from pediatric to adult medicine for young adults [ 57 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…respond to the eHQ, have more health problems, especially mental health issues, than non-participants [30]. However, in most previous studies, psychological issues of college students have been associated with restrains in seeking medical services [31][32][33]. It should be considered that the health examination process of the FSHS may provide the students a low threshold gateway to mental health services.…”
Section: Discussionmentioning
confidence: 99%